Novel methodologies for determining a suitable polymer for effective sludge dewatering. Issue 4 (August 2018) - To, Vu Hien Phuong; Nguyen, Tien Vinh; Vigneswaran, Saravanamuthu; Bustamante, Heriberto; Higgins, Matthew; van Rys, Derek
Highlights: The factors influencing optimal polymer demand (OPD) are determined. New method for selecting an appropriate polymer for conditioning and dewatering. Application of new methods for determining maximum cake solids content and OPD. Abstract: Understanding the interactions between sludge particles and polymers during sludge dewatering is necessary to: firstly, maximize dewatered cake solids content; and secondly, minimize polymer demand. In this study, two scientific methodologies, namely the 'y–intercept' concept and Higgins modified centrifugal technique (Higgins MCT) were used to identify the optimum polymer demand and type for effective conditioning and dewatering. Results from the 'y–intercept' concept show that a large amount of polymer required during conditioning of anaerobically digested sludge (ADS) is mainly due to neutralization of soluble biopolymers. In contrast, conditioning of aerobically digested sludge (AEDS) and waste activated sludge (WAS) is mostly controlled by a polymer bridging mechanism. The results indicated that, in order to achieve maximum dewatering performance with minimum conditioning polymer requirement, high charge density polymers are suitable for ADS while branched (or cross–linked) polymers can be used for AEDS and WAS. The new lab–scale technique, Higgins MCT, was successfully implemented for measuring cake solids content achievable by centrifuge and determining the optimum polymer demand (OPD). The Higgins MCT also helped to understand the relationship between digestion, conditioning and dewatering.